Distributed Global Functional Connectivity Networks Predict Responsiveness to L-DOPA and Subthalamic Deep Brain Stimulation. (1st September 2019) - Wu, Chengyuan; Foltynie, Thomas; Limousin, Patricia; Zrinzo, Ludvic; Akram, Harith
Abstract: INTRODUCTION: Brain circuit dysfunction in Parkinson's disease (PD) involves an extensive global network. A distinctive basal ganglia resting-state functional connectivity (rsFC) pattern has been linked with the ranked response to L-DOPA. We therefore sought to investigate global rsFC patterns associated with response to L-DOPA and to subthalamic nucleus (STN) deep brain stimulation (DBS) in patients with advanced PD. METHODS: A total of 19 patients underwent 3-Tesla resting-state functional magnetic resonance imaging (rsfMRI) in the ON-medication state prior to STN DBS. Improvement in UPDRS-III hemibody scores were assessed following L-DOPA therapy and STN DBS. Global rsFC was measured between regions-of-interest (ROIs) defined by the Automated Anatomical Labeling (AAL) atlas and the Montreal Neurologic Institute (MNI) PD25 subcortical atlas. Seed- and network-level correlations were made with an FDR- P < .005. Graph theoretical analysis was performed with an analysis threshold of FDR- P < .005; and then looking at the top 15% of edges. RESULTS: Response to L-DOPA and to DBS displayed cerebellar desynchronization with bilateral thalami and synchronization with bilateral ventromedial prefrontal cortices (vmPFC). L-DOPA response was additionally associated with desynchronization between the vmPFC and the fusiform gyrus. Meanwhile, DBS response was associated with more widespread areas, which have been implicated in visuomotor control and planning. Graph theory analysis revealed that DBS response was inversely related to global efficiency of the thalamus and putamen bilaterally. No significant graph metrics were found relative to L-DOPA response. CONCLUSION: Response to DBS and to L-DOPA share similar characteristics, particularly in cerebello-thalamo-cortical circuits, including those that play a role in planning, learning, decision-making, and reward-based behavior. Preservation of distributed networks involved in visuomotor control and network integration of striatothalamocortical circuits appear to predict DBS response. These findings shed a light on the mechanism of action of DBS and L-DOPA and may help serve as useful treatment response biomarkers.